2012
DOI: 10.1038/ejhg.2011.247
|View full text |Cite
|
Sign up to set email alerts
|

ironXS: high-school screening for hereditary haemochromatosis is acceptable and feasible

Abstract: As the results of the Human Genome Project are realised, screening for genetic mutations that predispose to preventable disease is becoming increasingly possible. How and where such screening should best be offered are critical, unanswered questions. This study aimed to assess the acceptability and feasibility of genetic screening for preventable disease, using the model of hereditary haemochromatosis, in high-school students. Screening was offered for the HFE C282Y substitution to 17 638 students. Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…‘Peer pressure' has been reported as a reason to participate in high-school carrier screening, 49 although a study offering hereditary haemochromatosis in the high-school setting showed that <1% of the students indicated that the decisions of their friends/peers influenced their participation in screening. 120 …”
Section: The Carrier Screening Testmentioning
confidence: 99%
“…‘Peer pressure' has been reported as a reason to participate in high-school carrier screening, 49 although a study offering hereditary haemochromatosis in the high-school setting showed that <1% of the students indicated that the decisions of their friends/peers influenced their participation in screening. 120 …”
Section: The Carrier Screening Testmentioning
confidence: 99%
“…There was no difference in any measure of anxiety, affect or health perception between CY and CC individuals 1 month after receiving results (Table 1). (1) to extremely (5). The two subscales therefore have a scoring range of 10-50 where a higher score indicates greater affect.…”
Section: Resultsmentioning
confidence: 99%
“…The overall methods of the ironXS study have been presented in detail previously . Screening results were provided to parents and students via their home contact details.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations